PENGARUH FEE AUDIT, AUDIT TENURE, ROTASI AUDIT DAN UKURAN PERUSAHAAN TERHADAP KUALITAS AUDIT - Nur Andika Handayani; Rudy Rudy (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine The Effect of Audit Fee, Audit Tenure, Audit Rotation and Company Size on Audit Quality. The population in this study are Mining Companies listedon the indonesian Stock Exchange for the 2017-2021 period. With the number of companies as many as 14 compinies and 70 observation. The tecnique in selection using purposive sampling. The result of processing analysis is Fee Audit, Audit Tenure, Audit Rotation and Company Size have a significant on Audit Quality. As for The result of this study is Fee Audit and Audit Tenure does not affect significant the Audit Quality, While Audit Rotation and Company Size does affect significant the Audit Quality